Quenching Process Optimization of Leaf Springs as Tengkuit Material using the Taguchi Method Approach - Gunawan, Indra; Putri, Fenoria; Junaidi, Subarkah (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Tengkuit is a traditional tool used by farmers to care for katuk, chilies, lumai, and others. The problem that farmers complain about is frequent wear and tear and chipping, which according to farmers and craftsmen must maximize quality and this must increase production costs and farmers' expenses. As time goes by, innovations have been made by humans to increase the durability of an object or material by increasing its hardness to save or reduce production costs. This research used qualitative approach with the taguchi method. The Taguchi method is a new engineering technique that aims to improve product and process quality while minimizing costs and resources. Taguchi's experimental design is more efficient because it allows searches involving many factors and numbers, and has good large-scale violent response. The maximum check value is the optimal parameter value for the tengkuit making process. Temperature and cooling media are very influential factors in testing hardness for making tengkuit. The results of the hardness research were shown as the lowest hardness value at a temperature of 600°C, with well water cooling media with a value of 24.3 HRC, and the highest hardness value at a temperature of 800°C. with bromus oil cooling media at a temperature of 700 ° C and a hardness value of 42.9HRC.